Abordagem multiescala para avaliação da ocupação de abelhas sem ferrão em fragmentos florestais de Mata Atlântica - Arena, Mariana Victorino Nicolosi (Universidade Federal de São Carlos, 2018)
Studies at multiple scales are essential to obtain a holistic view of bee conservation. For the accomplishment of these studies, the importance of analyzes that evaluate the composition of the landscape, the habitat factors and the abiotic factors must be considered. This study aimed to develop models for identification of hotspots for stingless bees in forest patches, and to address possible factors that influence the presence of native bees. The study was conducted in Salto de Pirapora - SP, a municipality composed of small fragments of Atlantic Forest. The spatial model was developed based on fragment size, core size, distance from the nearest forest patch and distance from the nearest body of water. From the spatial model, 3 hotspot forest patches (with characteristics that favor the presence of stingless bees with arboreal nesting habit) and 3 control fragments (considered fragments with unfavorable characteristics) were selected, and the presence of bees was evaluated from the occupation of artificial hives installed in the fragments. The analysis of the artificial hives showed that bees were influenced by competition for nesting sites, by predation and by precipitation. The microclimatic analyzes resulted in very variable data and did not demonstrate a significant relation to the presence of bees. Concerning the local scale, the structure of the vegetation showed great importance to the occupation of the artificial hives, with emphasis on the height and diameter of the trees where the hive was installed and the presence of shrubs and grasses as foraging resources. Bees showed preference to occupy artificial hives that were located in the patches’ core. The analysis of the surroundings of each patch was an essential factor for the development of the spatial model, demonstrating that the silviculture activity was beneficial for the presence of bees and the presence of pastures and grasslands was a negative factor. The study suggests that, for the elaboration of multiscale approaches, it is essential to evaluate not only the size of the fragment and the presence of water bodies, but also the quality of foraging (flowers) and nesting (size of trees) resources and the surroundings of the fragment. The study provided content so that the information can be extrapolated to other scenarios and encourages the conservation of the small forest patches as a strategy for the conservation of stingless bees.
Multiscale approach to evaluate the occupation of stingless bees in Atlantic Forest patches
Keywords: Meliponini; Paisagem; Conservação; Cobertura de terra; CIENCIAS BIOLOGICAS::ECOLOGIA